Evaluation of Outcomes of Surgical Treatment of Herniated Discs in the Lumbar Spine by Different Methods on the VAS and Oswestry Scales - Uleshchenko, D.V.; Shevchuk, A.V.; Stashkevych, A.T.; Bublik, L.O. (TERRA ORTHOPAEDICA, 2022)
Summary. Relevance. Despite the long-term use of microdiscectomy (OLM) for the surgical treatment of lumbar disc herniation, the recent rapid development of endoscopic methods has significantly increased their popularity. Objective: to evaluate the outcomes of surgical treatment of disc herniation in the lumbar spine using different methods (microdiscectomy vs. endoscopy) according to the VAS and Oswestry scales. Materials and Methods. The analysis of outcomes of 54 patients who underwent a standard microdiscectomy (mean age 41.1±11.7 years; 23 (42.6%) male and 31 (47.4%) female patients) was compared to the analysis of 35 patients after two – monoportal (n=13) and bi-portal (n=22) – modifications of endoscopic nucleotomy (mean age 43.1±13.1 years; 22 (75.9%) male and 13 (24.1%) female patients). Results. No significant difference appeared between these two groups of methods. Lumbar pain values according to VAS dropped from 5.9±1.59 to 3.4±1.55 on the first day after the surgery, and to 2.5±2.1 six months thereafter in the OLM group, compared to the decrease from 8.7±5.3 to 3.6±0.9 on the first after-surgery day and to 2.6±2.0 six months later after the endoscopic methods. Radicular pain according to VAS decreased on average from 8.5±1.17 to 1.3±1.04 on the first day after the surgery and to 1.4±1.6 six months later in the first group, compared to the decrease from 6.9±1.3 to 4.3±1.0 on the first day and to 2.2±1.9 six months thereafter in the second group. The quality of life in the OLM group according to the ODI improved on average from 74.4±5.12 before treatment to 29.7±9.6 in 1 month and to 9.6±9.2 six months after the surgery, compared to the score of 48.8±9.7 before treatment, 32.5±8.3 one month after the surgery, and 9.0±8.4 six months after the surgery (р<0.05) in the group of endoscopy. Conclusions. Significantly similar outcomes of treatment of patients with lumbar disc herniation using both endoscopic techniques and microdiscectomy were found. Regularities of reduction of radicular and lumbar pain syndrome on the VAS scale and improvement of quality of life on ODI at different follow-up terms for each of the groups have been established. The advantage of endoscopic surgical techniques over microdiscectomy, which reduces the duration of hospitalization with the same clinical effect, was found. Prospects for further research are to develop a differentiated approach to the treatment of this pathology.